Eye-Opening Medical Missions - Ethan Waisberg (University Library System, University of Pittsburgh, 2022)
Before choosing a specialty, medical students should obtain clinical exposure to that area. But how can a medical student do that, when clinical placements are years away, at the end of medical education? This article details a personal story about an experience on a medical mission trip and explains how these trips can benefit underserved populations,  and medical students by gaining early clinical exposure.